Structuring and creating alternatives for the eggplant loss problem using the value-focused thinking methodology (2020)
The eggplant is a short shelf-life vegetable whose export in Mexico generates significant incomes for horticultural companies. However, when the market’s price is down, or its quality does not fulfill the market’s requirements, eggplant is not exported, and demand is low in the domestic market. This situation generates financial problems for companies, unemployment for people, and environmental problems, among others. To reduce eggplant loss is necessary to understand the elements around the issue, structure the problem, and generate solution alternatives. In this work, the Value-Focused Thinking (VFT) methodology was applied in a horticultural farm in Sinaloa, Mexico, to obtain values from a decision-maker to structure the eggplant loss problem, objectives of the farm and generate solution alternatives. This article presents a structured problem about eggplant loss, which includes one strategic objective, five fundamental objectives, and nine means-ends objectives as well as twenty-seven solution alternatives such as applying protected agriculture technology, selling waste as food for livestock and designing a new product based on eggplant. Through the results of the application of VFT methodology, the decision-maker had a better understanding of the eggplant loss problem and its value, which is going to be reflected in benefits for the horticultural farm. Keywords: Eggplant loss, problem structuring, creating alternatives, value-focused thinking. JEL classification: D46, D81 Received: 10/06/2020. Accepted: 06/11/2020.  Published: 01/12/2020